"Click" hyaluronan based nanohydrogels as multifunctionalizable carriers for hydrophobic drugs. (15th October 2017) - Manzi, Giuliana; Zoratto, Nicole; Matano, Silvia; Sabia, Rocchina; Villani, Claudio; Coviello, Tommasina; Matricardi, Pietro; Di Meo, Chiara
Highlights: Amphiphilic polymers prepared with hyaluronan and riboflavin were synthesized by a click-chemistry reaction. These products were able, in aqueous media, to spontaneously self-assemble in nanostructures. The obtained nanogels were capable to load hydrophobic model drugs with a high efficiency. These nanogels were further functionalized very easily with PEG chains. Abstract: Highly hydrophilic and biocompatible nanocarriers based on polysaccharide hydrogels (nanohydrogels, NHs) were shown to be promising systems for drug delivery applications. Following the idea of these emerging drug carriers, the aim of the present work was to develop self-assembled hydrogel nanoparticles based on amphiphilic derivatives of hyaluronic acid (HA) and riboflavin (Rfv), synthesized by "click" Copper(I)-catalyzed Azide-Alkyne Cycloaddition (CuAAC) reaction. The obtained amphiphilic product (HA- c -Rfv) was able to form nanohydrogels in aqueous environments, in particular by applying an innovative autoclave-based method. HA of different molecular weights (Mw ) and degrees of substitution (DS) were prepared and the effect of these parameters on the NHs formation was assessed. The derivative HA 220 - c -Rfv 40/40 was chosen as the most interesting system, capable to form NHs in the range of 150–200 nm and with a negative ζ-potential. NHs were very stable in water solutions and, by adding dextrose as cryoprotectant, it was also possible to freeze-dry the NHs formulation. The developed system is proposed for the delivery of hydrophobic drugs; for this purpose, dexamethasone, piroxicam and paclitaxel were used as model drugs; these molecules were loaded into NHs with high efficiency by film-hydration technique. Furthermore, a HA- c -Rfv derivative bearing an excess of propargylic portions was capable to react with other N3 -derivatized molecules, opening the route to a wide spectrum of functionalization opportunities: in this direction, PEG-N3 has been tested as a model molecule for the preparation of PEGylated NHs.